Automatic Conversion of Software Specification into a Gantt-chart subject to Organization's Constraints - Dayani, M.; Gelbard, R. (Procedia computer science, 2015)
The current work introduces a model that integrates organizational constraints and policies when converting software specifications into a Gantt chart of the development process planned for that software specification. Typically, a system analyst and a software development project manager interact through software specifications, which are usually involved using a CASE tool in modeling the system. The project manager re-analyzes the model, extracts a work breakdown structure (WBS), and edits it to obtain a new Gantt chart incorporating resource allocations, cost considerations concerning outsourcing, matching each task to an appropriate qualification, setting priorities for each task, assigning safety buffers for each resource or task, setting dependencies between tasks, considering task risk assessments, identifying tasks that can be broken down into parallel subtasks, and determining organizational constraints that have to be taken into consideration.